ANALISIS SEMIOTIKA DARI LIRIK LAGU ESOK KAN BAHAGIA YANG DIPOPULERKAN OLEH GROUP BAND D’MASIV - Trinanda, E.Regi; Abidin, Sholihul (SCIENTIA JOURNAL, 2019)
The song "Esok kan Bahagia" was created by the band's vocalist D'Masiv Rian Ekky Pradipta and popularized by D'Masiv along with artists who joined Musica Studio's musical management. This song was originally created Rian based on his life experience, but adjusted to the social reality that occurred in Indonesia in 2014 that is the number of natural disasters that take casualties. Semiotics Analysis of the Song Lyrics "Esok kan Bahagia" popularized by Group D'Masiv Band is using data analysis techniques semiotics Ferdinand de Saussure. In Saussure's theory explains that sign (sign) is divided into two parts, namely signifier (signifier) and signified (signified). Sign here that many people know that the full lyrics of the song is a piece of writing to be sung. While the marker is a lyric that contains meaning. Signs are the result of lyrics analysis into a meaning. This study aims to see how the meaning process of song lyrics of the signifier (signifier) to be a sign (signified). And what is the meaning of the motivational message that the song lyricist wants to convey to the listener. Then, the meaning of motivation is adapted to Victor Vroom's motivational theory with the expectation perspective. The approach taken in this research is qualitative approach, by analyzing the song lyrics using the theory used, then drawn the conclusion using the result of analysis.